Housing Programmes And Urbanization : A Comprehensive Literature - Rameli, Norizan (Journal of Techno-Social, 2020)
The urbanization causing the number of residents in the city increase turn out to be a global issue. It gives impact towards the quality of life of the residents as a whole. One of the component in the life quality index is about housing, thus it is important to re-evaluate the needs of providing housing to the residents in the city, especially for low income group in Kuala Lumpur. The public housing program namely Program Perumahan Rakyat (PPR) Dimiliki and PPR Bersepadu are among the programs that help the low income group to have their own homes in Kuala Lumpur. Besides giving access to accommodation, the program is able to enhance the life quality indicator of the town folks. Nevertheless, a proper effective and comprehensive planning and administrations of the housing is very much needed to handle the urbanization challenges to ensure sustainable development is achieved.